2020
DOI: 10.1017/s1368980020002165
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and acceptance of interventions aimed at reducing sugar intake in Portugal

Abstract: Objective: Governments worldwide have been implementing interventions aimed at improving citizens’ dietary habits. Examining how individuals perceive these interventions is relevant for promoting future policies in this area, as well as informing the way they are designed and implemented. In the current study, we focused on interventions aimed at reducing sugar intake in Portugal, given the current high sugar consumption patterns in the population. Design: Online survey to assess which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…(2018) found that sugar consciousness as measured by the question “How much attention do you pay to the sugar content in your diet?”, was one of the strongest factors that influenced acceptance of government interventions to reduce sugar intake in French‐speaking regions of Switzerland. Similarly, another study conducted in Portugal reported that sugar‐consciousness; as assessed using the same question showed a positive correlation with the acceptance of interventions aimed at reducing the sugar‐intake (Prada et al., 2020). This suggests that individuals who are more aware of their sugar intake are likely to be more motivated to reduce their sugar consumption, thereby displaying greater support for interventions aimed at the same goal.…”
Section: Discussionmentioning
confidence: 86%
“…(2018) found that sugar consciousness as measured by the question “How much attention do you pay to the sugar content in your diet?”, was one of the strongest factors that influenced acceptance of government interventions to reduce sugar intake in French‐speaking regions of Switzerland. Similarly, another study conducted in Portugal reported that sugar‐consciousness; as assessed using the same question showed a positive correlation with the acceptance of interventions aimed at reducing the sugar‐intake (Prada et al., 2020). This suggests that individuals who are more aware of their sugar intake are likely to be more motivated to reduce their sugar consumption, thereby displaying greater support for interventions aimed at the same goal.…”
Section: Discussionmentioning
confidence: 86%
“…Our results must be interpreted with caution, due to the characteristics of our sample. As in other studies conducted with volunteers in the health and nutrition domain [ 22 , 46 ], our sample included a higher proportion of women and individuals with higher education. Another limitation of the current study concerns the rating task, which included a limited list of possible health conditions [ 29 , 30 ] related to excessive sugar intake.…”
Section: Discussionmentioning
confidence: 99%
“…This study was part of a broader project about eating behavior (for other instruments and results, see [ 22 , 33 ]), and we only focus on the relevant measures for the current paper. All procedures were reviewed and approved by an ethics committee of the Iscte-Instituto Universitário de Lisboa (approval #22/2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation